Infiltrating syringomatous adenoma of the nipple: Sonographic and mammographic features with pathologic correlation. Issue 7 (19th March 2014) - AlSharif, Shaza; Tremblay, Francine; Omeroglu, Atilla; Altinel, Gulbeyaz; Sun, Simon; Mesurolle, Benoît
ABSTRACT We report the case of a 39‐year‐old woman complaining of painless unilateral nipple enlargement for 3 weeks. She had no family history of breast cancer. Clinical examination revealed left nipple enlargement without pain, erythema, or skin changes m no associated palpable breast or axillary masses. Ultrasound showed several bright foci in the left nipple suggestive of microcalcifications. Neither solid nor cystic masses were detected. The mammogram performed subsequently confirmed the presence of multiple pleomorphic microcalcifications within the nipple. Wedge biopsy showed a syringomatous adenoma. Wide local excision of the nipple was performed. The postoperative course was uneventful. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:427–429, 2014